2014
DOI: 10.1186/1756-0500-7-894
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the quality of clinical veterinary services for Cattle: an application of a role play experiment in rural Uganda

Abstract: BackgroundThe dominance of veterinary paraprofessionals in the animal health markets has been linked to the decline in quality of veterinary services. This study uses a role play experiment to analyze how the interaction of farmers and service providers influences the quality and the demand for clinical services for cattle. The quality of clinical services was measured by scoring the accuracy of the service provider prescribing the appropriate drug for selected cattle diseases.MethodsThe game was played in fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The survey demonstrated a large unmet demand for advice on livestock in the selected countries. This agrees with the findings of the Platform for Agricultural Risk Management (PARM), which identified livestock pests and diseases among the most severe agricultural risks in Uganda [16], yet animal health services are understaffed, particularly in remote areas, and of insufficient quality [17]. Only few queries were on zoonoses in our survey, despite that endemic zoonotic diseases (such as leptospirosis, cysticercosis, tuberculosis, rabies, leishmaniasis, brucellosis) are estimated to cause more than 2.2 million human deaths globally and 2.4 billion cases of illness annually, and disproportionately affecting the poor in the Global South [18].…”
Section: Towards More Integration Of Health Servicessupporting
confidence: 88%
“…The survey demonstrated a large unmet demand for advice on livestock in the selected countries. This agrees with the findings of the Platform for Agricultural Risk Management (PARM), which identified livestock pests and diseases among the most severe agricultural risks in Uganda [16], yet animal health services are understaffed, particularly in remote areas, and of insufficient quality [17]. Only few queries were on zoonoses in our survey, despite that endemic zoonotic diseases (such as leptospirosis, cysticercosis, tuberculosis, rabies, leishmaniasis, brucellosis) are estimated to cause more than 2.2 million human deaths globally and 2.4 billion cases of illness annually, and disproportionately affecting the poor in the Global South [18].…”
Section: Towards More Integration Of Health Servicessupporting
confidence: 88%
“…This is exacerbated by the fact that in most African countries such as Uganda, there inappropriate limited diagnostic facilities including antimicrobial sensitivity testing ( 10 ). Previous studies in Uganda by Dione et al ( 17 ) and Ilukor and Birner ( 18 ) reported that incorrect diagnosis, under-dosing and overdosing and wrong drug administration routes, poor handling and storage of drugs were common practice among farm households and service providers in pig and cattle production systems, respectively. In fact, service providers were found not to be able to prescribe correct drugs for treatment of specific cattle diseases ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Uganda by Dione et al ( 17 ) and Ilukor and Birner ( 18 ) reported that incorrect diagnosis, under-dosing and overdosing and wrong drug administration routes, poor handling and storage of drugs were common practice among farm households and service providers in pig and cattle production systems, respectively. In fact, service providers were found not to be able to prescribe correct drugs for treatment of specific cattle diseases ( 18 ). Although the link between stakeholder practices and AMR is still weak, according to Ayukekbong et al ( 10 ), the lack of appropriate quality control regulations as reported in the distribution of veterinary of drugs including antimicrobials could be a contributing factor to the misuse of antimicrobials; consequently, any imprudent practice along drug supply chain may fuel the emergence of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Ilukor and Birner [ 38 ] ascertained that ‘livestock farmers who have no skills or training in veterinary science are not able to measure the quality of services being offered’ [ 38 ] (p.1) and, as a result, this inability to assess service quality might negatively impact upon their willingness to pay a fee to see them. This might lead to highly qualified practitioners being forced to accept low prices within certain markets, ultimately nudging them out of such areas altogether.…”
Section: Discussionmentioning
confidence: 99%